2016
DOI: 10.1097/mjt.0000000000000191
|View full text |Cite
|
Sign up to set email alerts
|

Sequential Therapy or Standard Triple Therapy for Helicobacter pylori Infection

Abstract: The effectiveness of standard triple therapy (STT) for the eradication of Helicobacter pylori has decreased recently. Sequential therapy (SQT) is a new regimen proposed to address this problem. The aim of this study was to compare the efficacy of SQT versus STT for H. pylori eradication. We searched The Cochrane Library, MEDLINE, Web of Science, and EMBASE databases up to July 2014. The risk ratios (RRs) of eradication rate were pooled, with a 95% confidence interval (CI). Thirty-six randomized clinical trials… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
21
1
4

Year Published

2017
2017
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(28 citation statements)
references
References 48 publications
1
21
1
4
Order By: Relevance
“…23 In a meta-analysis from Gatta et al, 16 ST was superior to 7-day and 10-day TT, but no advantage of ST was observed if TT was prolonged for 14 days (eradication rates 80.8% vs 81.3%, respectively), reflecting an improvement between 5.0% and 9.8% 1,16 in TT eradication rates with a 14-day course, and these results were replicated subsequently in another meta-analysis by Feng et al 24 Prospective Western European studies directly comparing 14-day TT with 10-day ST are currently lacking.…”
supporting
confidence: 65%
“…23 In a meta-analysis from Gatta et al, 16 ST was superior to 7-day and 10-day TT, but no advantage of ST was observed if TT was prolonged for 14 days (eradication rates 80.8% vs 81.3%, respectively), reflecting an improvement between 5.0% and 9.8% 1,16 in TT eradication rates with a 14-day course, and these results were replicated subsequently in another meta-analysis by Feng et al 24 Prospective Western European studies directly comparing 14-day TT with 10-day ST are currently lacking.…”
supporting
confidence: 65%
“…However, in our series, the sequential therapy allowed a high eradication rate (89%), even though enrolled patients lived in a geographical area characterized by high clarithromycin resistance. This outcome was probably due to the presence of tinidazole-susceptible H. pylori strains [1,49,50]. Evidence suggests that the sequential therapy besides being highly effective (91.1% and 92.1% eradication rates at ITT and PP analysis) [9], can overcome the issue of clarithromycin resistance [47].…”
Section: Discussionmentioning
confidence: 99%
“…A further study from the United Arab Emirates also showed such a result (84.6% vs 68%) . Two systematic reviews and meta‐analyses of sequential therapy vs triple therapy found sequential treatment to be significantly more effective (82% vs 75% and 84.1% vs 75.1%, respectively) . However, on subgroup analysis, both confirmed no benefit for sequential when longer triple therapy regimens were used.…”
Section: Sequential Concomitant and Hybrid Therapymentioning
confidence: 93%